Understanding Students’ Perspectives About Human-Building Interactions in the Context of Smart Buildings - Berrocal Rojas, Allan Francisco (2023)
Smart buildings provide a variety of sensor-based services to support and enhance the quality of human activities. Advanced technologies such as robotics are increasingly added to smart buildings’ ecosystems, creating a need to incorporate affective computing techniques to augment the quality of human-building, and human-robot interactions. To better understand user’s needs and expectations about human-building interactions, we conducted a pilot study using a mixed methods approach combining short surveys and controlled laboratory activities. We recruited 66 participants and collected several data elements characterizing their perceptions and expectations about smart building services. This paper presents preliminary evidence showing acceptance of specific human-building interaction methods based on ambient-sensors information such as in-context voice, behavior, and emotion, recognition. We also identified a need for educational activities to promote the understanding of smart building concepts and their impact in modern society. These results can be leveraged to assist the design of future services that include human-building and human-robot interactions.